2017
DOI: 10.1103/physreva.95.033602
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of one-dimensional SU(4) and SU(6) fermions with attractive interactions

Abstract: Motivated by advances in the manipulation and detection of ultracold atoms with multiple internal degrees of freedom, we present a finite-temperature lattice Monte Carlo calculation of the density and pressure equations of state, as well as Tan's contact, of attractively interacting SU(4)-and SU(6)-symmetric fermion systems in one spatial dimension. We also furnish a nonperturbative proof of a universal relation whereby quantities computable in the SU(2) case completely determine the virial coefficients of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This approximate SU(4) symmetry for the attractive S-wave interactions suppresses the sign and phase oscillations of the matrix determinants. This has been studied in several papers, some of which also consider inequalities that can be proven as a consequence [51,52,17,53,38].…”
Section: Auxiliary Fields and Symmetriesmentioning
confidence: 99%
“…This approximate SU(4) symmetry for the attractive S-wave interactions suppresses the sign and phase oscillations of the matrix determinants. This has been studied in several papers, some of which also consider inequalities that can be proven as a consequence [51,52,17,53,38].…”
Section: Auxiliary Fields and Symmetriesmentioning
confidence: 99%
“…In 1D the 1/k 4 decay of the momentum distribution and the contact were investigated numerically and analytically for the Lieb-Liniger model [25][26][27][28][29][30][31][32][33][34][35][36][37][38], attractive and repulsive spin- 1 2 fermions [39][40][41][42][43][44][45][46][47][48][49][50], the fermionic polaron problem [43,[51][52][53], spin-1 2 bosons [39,54,55], spin-1 bosons [56,57], κ-component (κ > 2) fermions and mixtures [58][59][60][61][62], and impenetrable anyons [63][64][65]. Despite this intense activity a comprehensive set of Tan relations or an analytical derivation of the tail of the momentum distribution can be found in the literature only for the case of single-component bosons [5,33,…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39], placing the system on a Euclidean spacetime of extent N x × N τ periodic in the space and anti-periodic in (imaginary) time. As shown in Fig.…”
Section: Gaussian Noise and Tan's Contactmentioning
confidence: 99%
“…It was also shown that the contact appears in sum rules involving the shear and bulk viscosities, the superfluid density, and other response functions [28][29][30] (See also Refs. [31][32][33][34]). …”
Section: Introductionmentioning
confidence: 99%